Immune Checkpoint Inhibitors: Challenges and Potential Strategies - Ge, Tianyu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
With the rapid development of science and technology, the treatment of cancer is also constantly being upgraded, but the number of cancer patients continues to grow, this has led to an increasing emphasis on such diseases. Therefore, immune checkpoint inhibitors have become the focus of our research today. In tumor cell proliferation, immune checkpoints develop as one of the ways to assist tumor cells in immune escape, so the use of immune checkpoint inhibitors can activate T cells, reduce T cell function exhaustion and inability, and achieve the purpose of killing tumor cells. In recent years, the results of PD-1, PD-L1 and CTLA-4 inhibitors have also been widely used in the treatment of patients, new treatments based on these inhibitors are also emerging. Despite the success of the ICIs in some ways, however, the researchers still found a number of factors that hindered its continued development, for example, research gaps with overall low response efficiency, therefore, new treatments need to be better improved and designed. Consequently, the research topic of this paper is the problems encountered by immune checkpoint inhibitors in this field and their solutions.